Penggunaan Konjungsi Koordinatif pada Karangan Narasi Pengalaman Pribadi Siswa Kelas VII SMP Negeri 3 Kupang Tahun Pelajaran 2025/2026 - Oserla Indrinita Naru; John Darwis Fallo; Ronni M. Ndun; Richard Oematan (Kampus Akademik Publiser, 2026)
This study aims to describe students' ability in using coordinate conjunctions in personal experience narrative essays. This study employs a descriptive method with a qualitative approach. Data collection techniques were carried out through the assignment of writing personal experience narrative essays, which were then analyzed based on scoring guidelines covering five aspects, namely accuracy of meaning, organization/structure, variation of conjunctions, application of punctuation, and coherence of the story. The subjects of this study were 32 students of SMP Negeri 3 Kupang City, consisting of 17 males and 15 females. The results of this study indicate that students' ability in using coordinate conjunctions is still varied. In the aspect of accuracy of meaning, some students have been able to use conjunctions appropriately, but there are still students who use conjunctions excessively, thereby obscuring the meaning of sentences. In the aspect of organization/structure, most students have been able to compose sentences coherently, although sentences that are too long and less effective are still found. In the aspect of variation of conjunctions, some students are still limited in their use of conjunction types, which are dominated by the use of the conjunction